2020
DOI: 10.1097/prs.0000000000006562
|View full text |Cite
|
Sign up to set email alerts
|

A Report on the Representation of Women in Academic Plastic Surgery Leadership

Abstract: Background: The year 2017 marked the first year women comprised a majority of U.S. medical school matriculants. While more women are pursuing surgical training, within plastic surgery, there is a steady attrition of women advancing in leadership roles. The authors report the current status of women in academic plastic surgery, from trainees to chairwomen and national leadership positions. Methods: The Electronic Residency Applications Service, San Franc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 43 publications
1
76
0
Order By: Relevance
“…Studies have demonstrated disparity in female leadership and authorship in the field of general plastic surgery, and although the number of women entering the field is increasing, female authors lag behind those of other specialties and are scarce on editorial boards. [23][24][25][26][27] Although not directly queried in this cross-sectional analysis, etiologies for gender inequity in medicine and other fields include implicit biases, cultural attitudes, gender stereotyping, sexual harassment, work-life balance, career goals and satisfaction, and lack of female mentors. [28][29][30] Recognizing the gender differences in FPRS, we hope to inspire future strategies to overcome barriers to inequity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated disparity in female leadership and authorship in the field of general plastic surgery, and although the number of women entering the field is increasing, female authors lag behind those of other specialties and are scarce on editorial boards. [23][24][25][26][27] Although not directly queried in this cross-sectional analysis, etiologies for gender inequity in medicine and other fields include implicit biases, cultural attitudes, gender stereotyping, sexual harassment, work-life balance, career goals and satisfaction, and lack of female mentors. [28][29][30] Recognizing the gender differences in FPRS, we hope to inspire future strategies to overcome barriers to inequity.…”
Section: Discussionmentioning
confidence: 99%
“… 6 8 Women are underrepresented on the podium at plastic surgery educational meetings and are less likely to be considered in selection for prestigious awards. 9 , 10 However, women are not less career-oriented than men: a study of 149,000 adults in 142 countries carried out by the International Labor Organization found that 70% of women would prefer to be working in paid jobs, rather than caring for their families, or doing both. 11…”
Section: Discussionmentioning
confidence: 99%
“…[ 87 ] High income United States Retrospective review n = 123 Not reported 2020 A Report on the Representation of Women in Academic Plastic Surgery Leadership. [ 88 ] High income United States Retrospective review Not reported 2020 Gender and academic promotion of Canadian general surgeons: a cross-sectional study. [ 89 ] High income Canada Cross-sectional analysis n = 405 (111/294) 27% Not reported 2020 Gender Disparities Among Burn Surgery Leadership.…”
Section: Resultsmentioning
confidence: 99%